Efficacy of combination of tablet mifepristone and misoprostol for first trimester pregnancy termination at different gestational age - Bhojwani, Poonam; Meena, Pragati; Verma, Gajendra Singh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Medical method of abortion is a safe, effective and affordable method for first trimester termination. However, nausea, vomiting, diarhoea, excess bleeding and incomplete abortion are known side effects. The aim of study was to compare the success rate of abortions in both groups, to compare the induction-abortion interval in both groups and to study the side effects of the drugs. Methods: This study was conducted in department of obstetrics and gynecology, NIMS Medical College, Jaipur, India during June 2017-August 2017. Total hundred cases were taken and divided into two groups. Group A was gestational age upto 49 days, Group B was gestational age 50-63 days. Both groups were given tab. mifepristone 200mg. followed by 48 hrs. by 4 tablets of tab misoprostol. Results: The results of the given regimen were highly successful and complete abortion was achieved in 96% and 94% in group A and group B respectively. The difference between two groups was statistically not significant (p value =0.64). Failure rates were seen in only 4% of group A and 6% of group B. Pain abdomen was seen in 16% of group A and 38% of group B patients. The difference between both groups was statistically significant (p value=0.02). Nausea was seen in 10% of group A and 30% of group B patients. The difference between both groups is statistically significant(p value=0.018). Conclusions: First trimester pregnancy can be successfully terminated with combination of mifepristone and misoprostol upto 63 days (9 weeks) of pregnancy.